Tuberculosis in 0–5-year-old children following TB contact investigations: a retrospective study in a low burden setting - Pasqualini, Cassandre; Cohen, Laure; Le Roux, Enora; Caseris, Marion; Faye, Albert (Frontiers in Pediatrics, 2023)
Abstract Introduction: We assessed the risk of tuberculosis (TB), the management and the outcome of 0- to 5-year-old children after TB contact in a low burden setting. Method: All 0- to 5-year-old children attending the TB clinic of Robert Debre Hospital, Paris, France, for a TB contact investigation between June 2016 and December 2019 were included in this retrospective study. The risk factors for TB were assessed using univariate and multivariate analyses. Results: A total of 261 children were included. Forty-six (18%) had TB, including 37 latent tuberculosis infection (LTBI) and 9 active TB diseases. The prevalence of TB was 21% in high-risk contacts i.e household or close contact and regular or casual contact. There was no TB in intermediate- and low-risk contacts (0/42). Living under the same roof (OR 19.8; 95% IC 2.6–153), BCG vaccine (OR 3.2; 95% IC 1.2–8.3), contact duration > 40 h (OR 7.6; 95% IC 2.3–25.3) and sleeping in the room of the index case (OR 3.9; 95% IC 1.3–11.7) were independently associated with TB. BCG was no longer associated when the analysis was restricted to interferon gamma release assay results. In children without initial LTBI, antibiotic prophylaxis was not prescribed in 2- to 5-year-old children or in 32/36 (89%) of 0- to 2-year-old children who had intermediate- or low-risk contact. Overall none of them experienced TB. Conclusion: In our low prevalence setting, the risk of TB in 0- to 5-year-old children following a household or close contact was high. Further studies are needed to better assess prophylaxis recommendations in intermediate or low risk contact. Key words: tuberculosis, children, type of contact, risk factor, prophylaxis